Poverty and Quality of Life in the Digital Era Interdisciplinary Discussions and Solutions - Myridis, Nikolaos E. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book proposes new solutions to the problem of poverty, and begins with providing analyses. It bases most of the analyses and solutions in the context of the digital era. The book also follows, in addition to a scientific distribution, a spatial-geographical one: analyses of countries of the European Union as well as South Africa, while it referring to two main variables, television and art, as agents of poverty alleviation. The book places particular focus on how poverty is understood in the framework of Industry 4.0. It introduces a new expanded Multidimensional Poverty Index with more than 20 dimensions; moreover, it provides a mathematically based solution for the disposal of perishable food. Finally, it does not disregard the crucial aspect of the issue of poverty: that of education planning. This book is of interest to specialists in poverty research, from students to professionals and from professors to activists, without excluding engineers. .
Part 1. Poverty & Quality of Life in Industry 4.0 -- 1. (e) Analysis of Poverty and Quality of Life -- 2. Redistribution of Perishable Food as a Corporate Social Responsibility Tool that Confronts Poverty -- 3. Digitization and International Development: A Descriptive Analysis of the Networked Readiness Index in Eight European Union Countries -- Part 2. Poverty, (digital) Culture & Media -- 4. overty and Children in South Africa: The Promise of Equality. A Semiotic Analysis -- 5. (SJ(Bow Digital Poverty Affects Television Viewing Habits -- Part 3. Interdisciplinary Poverty -- 6. Embracing Poverty with Lifelong Learning -- 7. Art as a Tool of Tackling Poverty and Social Inclusion of Vulnerable Groups.s
Keywords: Quality of life; Well-being.; Social justice; Economic development; Econometrics; Quality of Life Research; Well-Being.; Social Justice; Development Studies; Econometrics